Case Report: Intraosseous arteriovenous malformation of the temporal bone presenting with drug-resistant seizures - Sharifi, Guive; Paraandavaji, Elham; Hajikarimloo, Bardia; Meybodi, Tohid Emami; Behjati, Jina; Nilipour, Yalda; Kazemi, Mohammad Ali; Mohammadi, Esmaeil; Khanbabazadeh, Sajjad (Frontiers in Surgery, 2025)
Intraosseous arteriovenous malformations (AVMs) are rare conditions characterized by the development of AVMs within bones, leading to a variety of symptoms. Temporal bone AVMs are exceedingly uncommon, as evidenced by the small number of reported instances in the medical literature. A 19-year-old male patient presented with persistent seizures that were unresponsive to pharmacological treatments administered over three years. Imaging revealed a non-enhancing lesion measuring 31 × 22 mm in the right temporal lobe, originating from the middle fossa and the right petrous apex. The patient underwent successful surgical resection of the lesion, with no intraoperative complications or postoperative neurological deficits. Diagnosis of AVM was made after intraoperative pathological investigation. Follow-up examinations showed a complete resolution of the patient's seizures. The management of these lesions is challenging and it requires personalized approaches, which depend on clinical presentation, lesion location, progression, and the patient's overall condition.